Analisis Efektivitas Biaya Penggunaan Kombinasi Doksetaksel Doksorubisin dan Kombinasi Siklofosfamid - Doksorubisin pada Pasien Kanker Payudara Stadium II di RSUD X Bungo Tahun 2022 - Permatasari, Jelly; Sutrisno, Denny; Khodijah, Siti Ayu (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
Breast cancer is cancer that occurs in the mammary glands due to cell malignancy or uncontrolled growth of cells from the gland cells and their ducts.Cancer treatment has consumed BPJS funding of approximately 7.6 trillion rupiah at 2019 – 2020 years. This study is needed to determine the ratio of treatment effectiveness and the average cost comparison of the drug combinations Doxetaxel-Doxorubicin and Cyclophosphamide-Doxorubicin at X Bungo General Hospital in 2022. Cost Effectiveness Analysis Method (Cost Effectiveness Analysis) is an analysis by looking at the effectiveness of treatment seen from medical record information and calculating the value of ACER and ICER.The object of this study is the Regional General Hospital (RSUD) in Bungo Regency. It is known that the component of direct medical costs is in the form of BPJS payments. Based on the ACER value, it shows that Cyclophosphamide - Doxorubicin has a lower ACER value than the ACER value for Doxetaxel - Doxorubicin. It can be concluded that Cyclophosphamide - Doxorubicin has a cost-effectiveness value, namely cost-effective and effective therapy compared to Doxetaxel - Doxorubicin.